2020
DOI: 10.3390/ijms21041360
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidences for the Interactions of Auxin, Gibberellin, and Cytokinin in Bent Peduncle Phenomenon in Rose (Rosa sp.)

Abstract: In roses (Rosa sp.), peduncle morphology is an important ornamental feature. The common physiological abnormality known as the bent peduncle phenomenon (BPP) seriously decreases the quality of rose flowers and thus the commercial value. Because the molecular mechanisms underlying this condition are poorly understood, we analysed the transcriptional profiles and cellular structures of bent rose peduncles. Numerous differentially expressed genes involved in the auxin, cytokinin, and gibberellin signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…For instance, the key transcription factors of auxin, CK, GA, and ABA signaling have been well investigated, and it has been suggested that AR formation in some plants is controlled by coordinated hormonal regulation via a series of complex interactions [21,27]. Auxin, as the core of the crossregulatory network [29], has confirmed that interactions of auxin signaling with CK, GA, and ABA exist, as seen in the studies of Arabidopsis roots [15,32,34], but the phytohormone regulation network in woody plants, such as C. paliurus, is still poorly understood during AR formation. In this study, our objectives were as follows: (1) figure out the best hormonebased formulas to promote AR formation in softwood cuttings of C. paliurus; (2) explore the relationship between the endogenous hormone dynamic and the AR formation of C. paliurus softwood cuttings; and (3) screen the key genes involved in hormonal regulation and construct an auxin cross-regulatory network.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For instance, the key transcription factors of auxin, CK, GA, and ABA signaling have been well investigated, and it has been suggested that AR formation in some plants is controlled by coordinated hormonal regulation via a series of complex interactions [21,27]. Auxin, as the core of the crossregulatory network [29], has confirmed that interactions of auxin signaling with CK, GA, and ABA exist, as seen in the studies of Arabidopsis roots [15,32,34], but the phytohormone regulation network in woody plants, such as C. paliurus, is still poorly understood during AR formation. In this study, our objectives were as follows: (1) figure out the best hormonebased formulas to promote AR formation in softwood cuttings of C. paliurus; (2) explore the relationship between the endogenous hormone dynamic and the AR formation of C. paliurus softwood cuttings; and (3) screen the key genes involved in hormonal regulation and construct an auxin cross-regulatory network.…”
Section: Introductionmentioning
confidence: 90%
“…It is reported that phytohormones regulate the AR formation process by providing inherent signaling for determining cell fates and responding to stresses [17]. In recent years, some studies tried to reveal the phytohormone regulatory network using transcriptomic analyses and RNA-seq technology, especially focusing on the key regulatory components involved in the hormone signaling pathway [17,32,33]. For instance, the key transcription factors of auxin, CK, GA, and ABA signaling have been well investigated, and it has been suggested that AR formation in some plants is controlled by coordinated hormonal regulation via a series of complex interactions [21,27].…”
Section: Introductionmentioning
confidence: 99%
“…Hypocotyls were fixed in FAA (3.7% formaldehyde, 5% acetic acid, and 50% ethanol by volume) for 24 h under vacuum, then dehydrated in an ethanol series (70, 80, and 90%) and processed as described previously [22]. Wax blocks were sectioned at 10 µm.…”
Section: Preparation and Observation Of Hypocotyl Paraffin Sectionsmentioning
confidence: 99%
“…xative for more than 24 hours under vacuum. The xed tissues were then dehydrated in an ethanol series (70, 80, and 90%) and processed as described [68]. Wax blocks were sectioned at 10 µm.…”
Section: Integrated Analysis Of Degs and Differentially Abundant Metamentioning
confidence: 99%